Voir l’invisible. Le problème de l’eikon de la philosophie grecque à la théologie chrétienne - Daniele Guastini (Images Re-Vues)
This essay studies the transformations undertaken by the concept of eikon, image, in the move from pagan Greek to Christian culture. The value and the signified that this notion acquired within the conceptual framework of Greek philosophy, from Socrates to Plato, from Aristotle to Plotinus, will be considered and confronted with the use this notion had in Christian doctrine and theology during its first centuries, looking in particular at St. Paul and his apostolic Letters. The echoes and practical consequences these theoretical differences have had on the formation of the iconographic tradition in the Greek and Christian world are contemplated from the modalities of figuration of the divine : the one (Greek) being fundamentally summed up in the idea of mimesis, the other (primitive Christian) in that of typos.